Studi Penggunaan Dynamic Cone Penetrometer untuk Mendukung Perencanaan Perkerasan Jalan di Lingkungan UM Jember - Budi, Galih Alnabawi Putra Amelinda Setia; Gunasti, Amri; Alfaries, M. Rifki (Bearing : Jurnal Penelitian dan Kajian Teknik Sipil, 2025)
This study aims to analyze the bearing capacity of the subgrade in the vicinity of Muhammadiyah University of Jember using the Dynamic Cone Penetrometer Test (DCPT) method as a basis for planning road pavement thickness. The testing was conducted at several locations by recording the cone penetration values due to falling loads (mm/impact) and converting them into California Bearing Ratio (CBR) values through an empirical approach. The test results showed that the average DCP value at point 1 was 76.58 mm/impact with a CBR of 2.19%, while at point 2 it was 79.67 mm/impact with a CBR of 2.08%. Both values indicate that the subgrade is classified as soft to very soft soil with low bearing capacity. Linear regression analysis between the DCP and CBR values produced a correlation coefficient (R) of 0.974 and a coefficient of determination (R²) of 0.948, indicating a very strong and significant relationship between the two parameters. Based on these results, it can be concluded that the DCPT method is effective for quickly and economically determining field CBR values and can serve as a reference in planning pavement thickness at the University of Muhammadiyah Jember.